Global‐Scale Observations of the Limb and Disk Mission Implementation: 1. Instrument Design and Early Flight Performance. Issue 5 (14th May 2020) - McClintock, William E.; Eastes, Richard W.; Hoskins, Alan C.; Siegmund, Oswald H. W.; McPhate, Jason B.; Krywonos, Andrey; Solomon, Stanley C.; Burns, Alan G.
Abstract: The Global‐scale Observations of the Limb and Disk (GOLD) is a National Aeronautics and Space Administration mission of opportunity designed to study how the Earth's ionosphere‐thermosphere system responds to geomagnetic storms, solar radiation, and upward propagating atmospheric tides and waves. GOLD employs an instrument with two identical ultraviolet spectrographs that make observations of the Earth's thermosphere and ionosphere from a commercial communications satellite owned and operated by Société Européenne des Satellites (SES) and located in geostationary orbit at 47.5° west longitude (near the mouth of the Amazon River). They make images of atomic oxygen 135.6 nm and N2 Lyman‐Birge‐Hopfield (LBH) 137–162 nm radiances of the entire disk that is observable from geostationary orbit and on the near‐equatorial limb. They also observe occultations of stars to measure molecular oxygen column densities on the limb. Here, we provide an overview of the instrument and compare its prelaunch and early flight measurement performance. Direct comparison of LBH spectra of an electron lamp taken before launch with spectra on orbit provides evidence that both cascade and direct excitation are important sources of thermospheric LBH emission. Plain Language Summary: The Global‐scale Observations of the Limb and Disk (GOLD) is a National Aeronautics and Space Administration mission of opportunity designed to study how the Earth's ionosphere‐thermosphere system responds to geomagnetic storms, solar radiation, and upward propagating tides on time scales as short as 30 min. GOLD employs two identical ultraviolet spectrographs that make observations of the Earth's thermosphere and ionosphere from a commercial communications satellite owned and operated by SES and located in geostationary orbit at 47.5° west longitude (near the mouth of the Amazon River). They make images of atomic oxygen 135.6 nm and N2 LBH radiances of the entire disk that is observable from geostationary orbit and on the near‐equatorial limb. They also observe occultations of stars to measure molecular oxygen column densities on the limb. Here we describe the GOLD instrument including its optical system and detector. Its performance was characterized in the lab before launch. We compare measurements of laboratory sources made then to observations of the thermosphere after launch and find good agreement. Key Points: GOLD makes thermospheric images of OI and N2 LBH emissions, ionospheric images of OI emission and observes O2 absorption on the limb An overview of the instrument design and performance based on laboratory characterization is provided Imaging and spectroscopic performance confirm laboratory results. Radiometric sensitivity using stars is ~20% less than ground measurement